Halal Certification in Slaughterhouses (RPH) Impacts on Halal Certification of Animal-Based Food Products - Mustahal, Muhamad (Fakultas Syariah INSURI Ponorogo, 2022)
Animal housing (RPH) plays a significant role in passing the halal certification of products based on animal ingredients. However, the awareness of RPH to certify halal RPH is still very low, so micro and small business actors feel they are getting halal-certified materials for their products. This research will focus on the regulation of halal certification in animal house services (RPH) and the expansion of MSE product certification. Many animal products require halal certification as a guarantee of the halalness of the product. Since the majority of users in Indonesia are Muslims, it is very important to provide food safety for them. This research is an analytical descriptive study using a qualitative approach. The results of this study indicate that the low factor of halal-certified abattoirs is due to several factors. The most dominant factor is that there is no pressure from the government or consumers, the second factor is because they feel that their slaughter is halal, and the third factor is the understanding without a halal certificate, even meat is already halal. And the fourth factor does not know about the halal certification. The conclusions of this study include: first, the law on halal certificates in the field of slaughterhouse services has not received serious attention from related parties, and second, the lack of halal certificated slaughterhouses for animal-based MSE products. Third, the need for more serious socialization to increase the awareness of RPH service owners on the importance of halal certificates for RPH. Suggestions from the results of this study are that each element related to RPH should pay more attention to the rules made by BPJH of the Ministry of Religion in ensuring the halalness of RPH, such as the Ministry of Trade and Industry, the Ministry of Cooperatives and SMEs and related agencies.